Comparing Activity and Effectiveness of (Ru/Pd), (Ru/Pt) Photocatalysts for Hydrogen Generation, Photochemical Reaction with HPLC - Hamid M. Younis , (Scientific Journal of University of Benghazi, 2020)
In this contribution recent developments in the design and application of Ru/Pd, Ru/Pt photocatalysts for the generation of hydrogen via intramolecular processes are assessed. The basic concepts of such assemblies are discussed together with an overview of the factors and molecular issues that affect their potential as photocatalysts. Issues that so far have limited progress are discussed and suggestions for future directions are made. The extent of localization of the emissive excited state was determined by HPLC chromatography and same wavelengths; however, whereas for Ru/Pd the emission is based on the Ru(tpy)Cl- center, for Ru/Pt the emissive state is localized on the Ru(bpy)2 unit. This indicates that also in the excited state there is efficient interaction between the two metal centers was characterized by both HPLC, Spectroscopy.